“Green Marketing”An Analysis of Strategy Approach, Challenges, and Opportunities for Business (Study Literature Review) - Helena Louise Panggabean; Sutrisno; Josua Panatap Soehaditama; Wenny Desty Febrian; Lira Agusinta; Ryan Firdiansyah Suryawan (Formosa Journal of Multidisciplinary Research, 2023)
The purpose of this article is to provide literature for a comprehensive understanding of eco-friendly and sustainable marketing in addition to the questions at hand. This qualitative study used a mini-review approach to achieve our research objectives. The green marketing mini-evaluation was done by reading and analyzing dozens of peer-reviewed journal articles. The first table contains information about the title of the article, author, publisher and year of publication The results of this study with proof and true corroboration that the concept of green marketing has been used in various business organizations with various gaps and phenomena.